THE EXTENDED STORAGE OF DILUTED CEMANI ROOSTER SEMEN USING EGG YOLK PHOSPHATE WITH THE ADDITION OF SUGARCANE JUICE - I Made Wahyu Chandra Bhadreswara; Wayan Bebas; I Wayan Sukernayasa (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Enhancing the population of Cemani chickens, a native Indonesian poultry genetic resource, requires reproductive technologies such as artificial insemination (AI). This study aimed to analyze the effect of storage duration on Cemani rooster semen diluted with a 20% egg yolk phosphate and 15% sugarcane juice formulation. A Completely Randomized Design (CRD) was employed with four storage periods (0, 24, 48, and 72 hours) at 5–7°C. Parameters observed included sperm motility, viability, and abnormalities. Results showed a decline in progressive motility from 80.33% (0 hours) to 54% (72 hours), viability from 88.17% (0 hours) to 62% (72 hours), and an increase in abnormalities from 5.17% to 9.33%. Despite the decline, all parameters remained within AI standards (motility >40%, abnormalities <20%) up to 72 hours. This study concludes that egg yolk phosphate and sugarcane juice combination is effective as a low-cost natural diluent for Cemani semen preservation. Further research is recommended to optimize diluent composition for longer storage.